1994
DOI: 10.1254/jjp.66.7
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Studies on the Inhibition of Degranulation of Rat Mast Cells by a Novel Anti-Allergic Agent, PTPC

Abstract: ABSTRACT-When rat mast cells sensitized by IgE antibody were exposed to antigen, transmission elec tron microscopy revealed alteration of the granules, cavity formation by fusion of the perigranular mem brane and granule release by the fusion of the cavity membrane with the mast cell membrane. Scanning elec tron microscopy disclosed the extrusion of smooth and round bodies from pores formed on the cell surface. These changes were accompanied by the release of histamine. The inhibition of this degranulation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
3
0
0
Order By: Relevance
“…Ohashi et al . also demonstrated the pores with average size at 600–800 nm and granules with average size of 600 nm on mast cells from mice by scanning electron microscopy, which were similar with the results we obtained by AFM imaging. Additionally, not all granules were released into the supernatant of RBL‐2H3 cells, because granules could also be observed on the substrate, at the edge of RBL‐2H3 cells (Supplementary materials Fig.…”
Section: Resultssupporting
confidence: 88%
“…Ohashi et al . also demonstrated the pores with average size at 600–800 nm and granules with average size of 600 nm on mast cells from mice by scanning electron microscopy, which were similar with the results we obtained by AFM imaging. Additionally, not all granules were released into the supernatant of RBL‐2H3 cells, because granules could also be observed on the substrate, at the edge of RBL‐2H3 cells (Supplementary materials Fig.…”
Section: Resultssupporting
confidence: 88%
“…Tizard and Holmes [12] studied degranulation of rat mast cells by scanning electron microscopy, and concluded that both exocytosis and pore formation on the cell surface were significant mechanisms for the degranulation. These observations were confirmed by the studies at other laboratories [13,14]. On the other hand, isolated human mast cells from several organ sources, such as lung [5] and skin [6], have been used to examine a regulated secretion by transmission electron microscopy, and anaphylactic degranulation of these isolated human mast cells characteristically showed extrusion of altered, membrane-free granules through multiple pores in the plasma membrane to the exterior of the cell [5,6].…”
Section: Discussionsupporting
confidence: 65%
“…On the basis of the published light and electron microscopic studies on rat mast cell activation [1,2,12], it seems likely that similar granule extrusions observed in the present phase-contrast microscopy studies using cinematographic techniques is indeed exocytosis. Scanning electron microscopic studies have confirmed this phenomenon and shown that IgE-mediated process we used in the present study yielded human mast cells with abundant exocytotic figures resembling those obtained from activated-rat mast cells [1,2,[12][13][14], indicating that the cultured human mast cells may contribute a great deal to mast cell research, such as signal transduction and regulation of mediator release, and these studies would require sequential biochemical and detailed ultrastructural analysis.…”
Section: Discussionsupporting
confidence: 56%